Investigating Teaching English for Deaf Students at SLB Negeri 1 Karangasem: Procedures and Challenges - Duniangella, Ni Komang Rutjayanthi Mayami; Santosa, Made Hery; Budiarta, Luh Gd Rahayu (Journal of Educational Study, 2024)
This study examines the procedures and challenges of teaching English to deaf students at SLB Negeri 1 Karangasem during the 2024/2025 academic year. Using a qualitative approach, it incorporates classroom observations and in-depth interviews with English teachers to analyze teaching methods, communication strategies, and lesson structuring. The findings reveal that teachers follow a structured nine-step procedure, including lesson preparation, clear visibility, structured speech, repetition, communication aids, visual reinforcement, written support, expressive communication, and comprehension checks. These strategies align with previous research emphasizing multimodal approaches in deaf education. Despite these structured methods, teachers face challenges such as limited student vocabulary, pronunciation difficulties, and low motivation due to the complexity of English. They combine sign language, visual media, interactive digital tools, and personalized learning techniques to address these issues and enhance engagement. The study underscores the importance of structured and adaptive teaching strategies in supporting deaf students' language learning. Additionally, it highlights the need for ongoing professional training for teachers in special education, equipping them with effective methodologies to improve instruction. These findings contribute to the broader field of special education, particularly in advancing English language teaching for students with hearing impairments.